Enzyme-mediated biodegradation of long-chain n-alkanes (C(32) and C(40)) by thermophilic bacteria - Elumalai, Punniyakotti (3 Biotech, 2017)
Removal of long-chain hydrocarbons and n-alkanes from oil-contaminated environments are mere important to reduce the ecological damages, while bio-augmentation is a very promising technology that requires highly efficient microbes. In present study, the efficiency of pure isolates, i.e., Geobacillus thermoparaffinivorans IR2, Geobacillus stearothermophillus IR4 and Bacillus licheniformis MN6 and mixed consortium on degradation of long-chain n-alkanes C(32) and C(40) was investigated by batch cultivation test. Biodegradation efficiencies were found high for C(32) by mixed consortium (90%) than pure strains, while the pure strains were better in degradation of C(40) than mixed consortium (87%). In contrast, the maximum alkane hydroxylase activities (161 µmol mg(−1) protein) were recorded in mixed consortium system that had supplied with C(40) as sole carbon source. Also, the alcohol dehydrogenase (71 µmol mg(−1) protein) and lipase activity (57 µmol mg(−1) protein) were found high. Along with the enzyme activities, the hydrophobicity natures of the bacterial strains were found to determine the degradation efficiency of the hydrocarbons. Thus, the study suggested that the hydrophobicity of the bacteria is a critical parameter to understand the biodegradation of n-alkanes.